1993
DOI: 10.1016/0022-1694(93)90119-t
|View full text |Cite
|
Sign up to set email alerts
|

The hydrological effects of fire in South African mountain catchments

Abstract: Stream-flow and storm-flow in four small catchments were analysed by the paired catchment method for a response to fire. Two of the catchments were vegetated with over-mature fynbos (the indigenous scrub vegetation of the southwestern Cape Province, South Africa) , one was afforested to Pinus radiata and the fourth to Eucalyptus fastigata. One of the fynbos catchments was burned in a prescribed fire in the late dry season. The other catchments burned in wildfires. Neither of the fynbos catchments showed a chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
3
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 55 publications
2
125
3
4
Order By: Relevance
“…Average annual streamflow discharge increased by about 10 percent to 4.8 inches (120 mm) on a 612 acre (245 ha) watershed in the Cape Region of South Africa following a wildfire that consumed most of the indigenous fynbos (sclerophyllous) shrubs (Scott 1993). This increase was related mostly to the reductions in interception and evapotranspiration losses.…”
Section: Effects Of Wildfiresmentioning
confidence: 99%
See 1 more Smart Citation
“…Average annual streamflow discharge increased by about 10 percent to 4.8 inches (120 mm) on a 612 acre (245 ha) watershed in the Cape Region of South Africa following a wildfire that consumed most of the indigenous fynbos (sclerophyllous) shrubs (Scott 1993). This increase was related mostly to the reductions in interception and evapotranspiration losses.…”
Section: Effects Of Wildfiresmentioning
confidence: 99%
“…A burn that was prescribed to reduce the accumulated fuel loads on a 450 acre (180 ha) watershed in the Cape Region of South Africa resulted in a 15 percent increase to 3.2 inches (80 mm) in average annual streamflow discharge (Scott 1993). Most of the fynbos shrubs that vegetated the watershed were not damaged by the prescribed fire.…”
Section: Effects Of Prescribed Burningmentioning
confidence: 99%
“…Fires in chaparral environments, such as in southern California, exhibited increased flows of up to as much as 2 orders of magnitude, with much of this occurring in the dry season (Coombs and Melack, 2013;Hogue, 2011, 2015;Loáiciga et al, 2001). Fires in other chaparral environments were found to also yield flow increases, such as in South Africa (Lindley et al, 1988;Scott, 1993), Cyprus (Hessling, 1999), and France (Lavabre et al, 1993). Additional increases to post-fire flow regimes were found in temperate, forested catchments as well (Neary et al, 2005;Watson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have documented total runoff increases under post-wildfire conditions (Benavides-Solorio and MacDonald, 2001;Inbar et al, 1998;Lavabre et al, 1993;Robichaud et al, 2000;Scott, 1993). For example, Lavabre et al (1993) used a lumped conceptual hydrological model to evaluate a small Mediterranean basin which experienced a burn covering 85 percent of its surface area in 1990.…”
Section: Model Performancementioning
confidence: 99%
“…They suggested a 30 percent increase in the annual runoff yield. Scott (1993) showed 25 total streamflow volume increases of 15.3 and 9.4 percent in response to burning in two small mountainous catchments using a paired catchment method. In contrast, Mahat et al (2015) reported no significant change between the modeled streamflow from burned and unburned models.…”
Section: Model Performancementioning
confidence: 99%